Perancangan Aplikasi Pengelolaan Data Penjualan dan Pemesanan di SKMart Berbasis Web - Rahayu, Sri; Kurniadi, Dede; W, Faksi Ahmad (Institut Teknologi Garut, 2023)
A sales and ordering data management application is very necessary in improving performance in a company. SKMart still applies conventional methods or uses manual methods in ledgers, which is in accordance with the results of interviews with the owner that using manual methods causes the process of managing sales and ordering data, searching for data and calculating transaction data to take quite a long time, even when data loss. The aim of this research is to design a web-based sales and ordering data management application that can make it easier for shop owners to manage data, record item data and recap each transaction. With a web-based sales and ordering data management application, it is able to make it easier for users (admins) to obtain the data needed so that the process of managing sales and ordering data that occurs at SKMart stores becomes efficient. Regarding improving this application, this research uses a methodology called RUP, the stages of which are inception, elaboration, contraction and transition. Then use Unified Modeling Language modeling. The result of this research is a web-based sales and ordering data management application, which is able to facilitate the management of information data needed by users (admins) to manage goods sales data, goods ordering data, transaction data.